Incremental prognostic value of hybrid [15O]H2O positron emission tomography–computed tomography: combining myocardial blood flow, coronary stenosis severity, and high-risk plaque morphology. (21st September 2020) - Driessen, Roel S; Bom, Michiel J; van Diemen, Pepijn A; Schumacher, Stefan P; Leonora, Remi M; Everaars, Henk; van Rossum, Albert C; Raijmakers, Pieter G; van de Ven, Peter M; van Kuijk, Cornelis C; Lammertsma, Adriaan A; Knuuti, Juhani; et al.
Abstract: Aims : This study sought to determine the prognostic value of combined functional testing using positron emission tomography (PET) perfusion imaging and anatomical testing using coronary computed tomography angiography (CCTA)-derived stenosis severity and plaque morphology in patients with suspected coronary artery disease (CAD). Methods and results : In this retrospective study, 539 patients referred for hybrid [ 15 O]H2 O PET-CT imaging because of suspected CAD were investigated. PET was used to determine myocardial blood flow (MBF), whereas CCTA images were evaluated for obstructive stenoses and high-risk plaque (HRP) morphology. Patients were followed up for the occurrence of all-cause death and non-fatal myocardial infarction (MI). During a median follow-up of 6.8 (interquartile range 4.8–7.8) years, 42 (7.8%) patients experienced events, including 23 (4.3%) deaths, and 19 (3.5%) MIs. Annualized event rates for normal vs. abnormal results of PET MBF, CCTA-derived stenosis, and HRP morphology were 0.6 vs. 2.1%, 0.4 vs. 2.1%, and 0.8 vs. 2.8%, respectively ( P  < 0.001 for all). Cox regression analysis demonstrated prognostic values of PET perfusion imaging [hazard ratio (HR) 3.75 (1.84–7.63), P  < 0.001], CCTA-derived stenosis [HR 5.61 (2.36–13.34), P  < 0.001], and HRPs [HR 3.37 (1.83–6.18), P  < 0.001] for the occurrence of death or MI. However, only stenosis severity [HR 3.01 (1.06–8.54), P  = 0.039] and HRPs [HR 1.93 (1.00–3.71), P  = 0.049] remained independently associated. Conclusion : PET-derived MBF, CCTA-derived stenosis severity, and HRP morphology were univariably associated with death and MI, whereas only stenosis severity and HRP morphology provided independent prognostic value. Graphical Abstract: